ANALISA DAMPAK PDB, SBI, KURS DAN INFLASI TERHADAP TINGKAT SUKU BUNGAKREDIT PADA PERBANKAN INDONESIA - Widiastuti Murtiningrum; Suharyanti Suharyanti (Sekolah Tinggi Manajemen IMMI, 2020)
The existence of banks is important in the business world. The link between the business world and bank financial institutions cannot be separated, especially in terms of investment and credit. The bank will distribute loans in the form of investment loans and working capital needed by the business world and continue to develop its competence to promote sustainable credit growth while carrying out its function as a financial intermediary service. Macroeconomic environment is an environment that affects the company's operational activities, therefore it is necessary to be able to understand and predict future macroeconomic conditions. For this reason, several macroeconomic indicators need to be considered in order to assist in making decisions. Macroeconomic indicators that are often linked in making decisions are Bank Indonesia interest rates, Rupiah exchange rates, inflation rates and MSME financing allocationsMany factors can affect the demand and lending by banks, both internal factors, namely the bank itself, such as the level of bad loans, lack of capital, and so on, as well as macro factors such as national income, interest rates, rupiah exchange rates, inflation and other factors . For this reason, a good understanding of the influence of these factors, particularly macro factors, is needed, and is expected to provide an explanation of the impact of the movement of these macro indicators on credit in Indonesian banks. This study aims to obtain empirical evidence about the analysis of the impact of the Gross Domestic Product, SBI Interest Rate, Rupiah Exchange Rate against the USD and Inflation Rate on the Interest Rates of the Indonesian Banking Credit. Secondary data were obtained from the annual published financial statements of the Persero Banks. The population used in this study is Conventional and Sharia Commercial Banks, Rural Banks and Sharia Rural Banks.The analysis technique used is multiple linear regression, and the hypothesis test uses the t test to test the coefficient of multiple linear regression, and the F test to test the effect simultaneously with a significance level of 5%. The classic assumption test was also carried out which included a normality test, a multicollinearity test, a heteroscedasticity test, and an autocorrelation test. In the Multiple Regression test, the variable SBI Interest Rate, Rupiah Exchange Rate against USD and Inflation Rate have a direct (positive) effect. While GDP has the opposite effect (negative). Data collection techniques using the method of literature that is by collecting library data. Data sources are textbooks, articles, journals, literature reviews and statistical data over time